Developing Culturally Responsive Programs to Promote International Student Adjustment: A Participatory Approach - Johnson, Laura R.; Seifen-Adkins, Tanja; Singh Sandhu, Daya; Arbles, Nadezda; Makino, Hitomi (Journal of International Students, 2018)
International students in the United States face acculturative stress, yet few seek counseling. In this paper, we highlight a participatory approach to develop culturally and contextually competent programs to enhance international student adjustment and engagement. We combined findings from the Acculturative Stress Scale of International Students (ASSIS) with interviews eliciting international student concerns and ideas for programming. On the ASSIS, randomly selected international students (n=40) expressed high levels of acculturative stress. These students, along with key informants (n=5) and international student leaders (n=8) formed focus groups, and provided suggestions for programs. Based on these formative results, we developed and described a variety of programs. Our experiences with participatory approaches suggest a promising avenue for enhancing cultural and contextual competence in international student programming.